Biased Voluntary Nutri-Score Labeling - Wendelin Schnedler; Antonia Vigano (ZBW - Leibniz Information Centre for Economics, 2024)
Food labels are supposed to quickly inform consumers about the nutritional values of products. We provide evidence that in a system where labels are voluntary, they are systematically distorted. The probability of finding a label on a product of the category with the highest nutritional value is 51 percentage points larger than in the lowest category.
Keywords: M38; D18; I18; 650; food labels; marketing; consumer protection